Jurisprudence of children's rights - Rajan, Amitabh (2009)
Moral norms and legal norms have complimentary functions in helping children grow adequately, but the state has the final role in ensuring that all networks and institutional arrangements of social cooperation work for the welfare of voiceless children are in place. The task before the governments is to reconcile the culture and public resources with universal consensus on children's rights and legislate a few more ones to rescue children from intolerable situations. This article analyses the discourses and institutional-legal mechanisms that focus on empowering children with rights of development, protection and participation among competing demands for resources, legal interventions and institutional support. - Reproduced.
Keywords: Rights of the child